Plastic deformation and fracture processes in metal/graphene composites: a review. Issue 5 (3rd September 2022) - Sheinerman, A.G.
Abstract: We provide a survey of the results of recent experiments, molecular dynamics simulations and theoretical models concerning the plastic deformation and fracture processes in metal-matrix composites reinforced with graphene platelets or graphene nanoribbons. We consider homogeneous metal/graphene composites with randomly oriented and aligned graphene platelets, as well as laminated metal/graphene composites. The focus of the review will be on the strengthening and strain hardening mechanisms of the composites and the results of modeling the processes of their plastic deformation and strength properties. We examine in detail the effects of the inclusion dimensions, characteristics of interfaces, and the presence of buffer layers between the metal matrix and graphene on strength and ductility of metal/graphene composites. We critically review various theories of strengthening of such composites and discuss the contradictory results that these theories predict. In addition, various plastic deformation and fracture processes, including dislocation interaction with graphene inclusions, grain and lamella boundaries, self-healing of the composites, and crack generation and growth, will be examined, and the influence of these processes on the mechanical properties of metal/graphene composites will be discussed. We demonstrate that the excellent mechanical properties of metal/graphene composites are related to their unique microstructure and the variety of strengthening and strain hardening mechanisms. We also discuss the effect of the bimodal grain size distribution of the metallic matrix on their strength and ductility. The summary will outline the conclusions and briefly highlight unresolved issues and prospects for further research.